The Correlation Between Depression and GERD-Q Score Among Dyspepsia Patient in Atma Jaya Hospital - Nadya Hanjani; Mario Steffanus (The Indonesian Society for Digestive Endoscopy, 2019)
Background: In adults, the symptoms of gastroesophageal reflux disease (GERD) are often complained of in daily life and their prevalence has increased. Symptoms of GERD are often found along with the occurrence of dyspepsia. One of the factors that affect the symptoms of GERD is depression. Due to the limited data available in Indonesia, this study was conducted to see the correlation between depression and gastroesophageal reflux disease questionnaire score (GERD-Q).Method: This study was conducted on dyspepsia patients at Atma Jaya Hospital (RSAJ) beginning at June to September 2018. The study was conducted using a cross-sectional design and using the GERD-Q and Depression questionnaire, Anxiety, Stress Scale 42 (DASS 42) which has been translated and validated by other researchers to measure GERD scores and depression scores.Results: The total respondents of this study were 53, with the percentage of men and women being 30.2% and 69.8% respectively. The average age of patients was 57.2, with those who were overweight / obese as many as 64.2%, and those who smoked as many as 9.4%. As many as 73.6% respondents had a GERD-Q score of ≥ 8. Moreover, 35.8% of respondents had mild depression, 15.1% had moderate depression, and 3.8% had severe depression. The results showed a significant correlation between depression and GERD-Q score in Atma Jaya Hospital dyspepsia patients (p = 0,000, r = 0,496).Conclusion: There is a correlation between depression and GERD-Q score of dyspepsia patients at Atma Jaya Hospital